2017
DOI: 10.1159/000489306
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability in E6 and E7 Oncogenes from Human Papillomavirus Type 58 in Mexican Women

Abstract: Background/Aims: The study aimed to describe human papillomavirus (HPV) 58 genetic variability in E6 and E7 oncogenes from women in southeast Mexico and their phylogenetic relationships with the sequences from other geographical regions. Methods: The E6-E7 region was amplified by nested PCR, and sequenced for identification of polymorphisms, phylogenetic trees construction, and haplotype and fixation tests. Results: HPV58 positive samples were obtained from a repository, 54 were amplified, 47 sequences for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…In contrast, this genotype was not found in any CC sample. The fact that PGMY amplification-based tests could not detect this genotype may be due to the variability reported for this genotype in Mexico and in some regions of the world (Raiol et al, 2009;Yue et al, 2013;Chen et al, 2016;Conde-Ferraez et al, 2017). HPVs 30, 214, and 11 were also common in this group.…”
Section: Discussionmentioning
confidence: 88%
“…In contrast, this genotype was not found in any CC sample. The fact that PGMY amplification-based tests could not detect this genotype may be due to the variability reported for this genotype in Mexico and in some regions of the world (Raiol et al, 2009;Yue et al, 2013;Chen et al, 2016;Conde-Ferraez et al, 2017). HPVs 30, 214, and 11 were also common in this group.…”
Section: Discussionmentioning
confidence: 88%
“…The most common synomous mutations observed in HPV58 E6 and E7 gene were C307T and T744G, which had also been reported in the past [44][45][46] . The C307T and T744G mutations were also common in other countries, such as Mexico, Korean and Italy 35,[47][48][49] . However, the variations included in the present study had been reported to have no association with cervical lesions 34,35,49 .…”
Section: Discussionmentioning
confidence: 95%
“…It’s worth mentioning that intratype variants of HPV types 31, 35, 62, and 58 have been also characterized from cervical samples of Mexican women from different states of Mexico [ 97 , 100 , 101 ]. Additionally, variations in HPV-51 have been analyzed in HIV positive Mexican patients, this viral type being highly prevalent in this group [ 102 ].…”
Section: Distribution Of Hpv Variants In Mexicomentioning
confidence: 99%